Prevalence of Depressive Symptoms and Associated Factors among Internal Migrants with Tuberculosis: A Cross-Sectional Study in China - Dong, Xiaoxin (Am J Trop Med Hyg, 2020)
There are hundreds of millions of internal migrants in China, and tuberculosis (TB) is an important health threat to them. However, the mental health problems of internal migrants with TB in China have been ignored. The present study aimed to determine the prevalence of depressive symptoms and its associated risk factors among internal migrants with TB in China. A cross-sectional survey was conducted between June 2018 and March 2019 in Shenzhen, southern China. Data were collected from 1,057 internal migrants with TB using a structured questionnaire. Depressive symptoms were measured using the Center for Epidemiologic Studies Depression Scale. Multinomial logistic regression analysis was used to identify risk factors for depressive symptoms. Of the 1,057 participants included in this study, 53.8% had depressive symptoms. Of these, 38.9% had mild, whereas 14.9% had moderate-to-severe depressive symptoms. Multinomial logistic regression analysis suggested that higher likelihoods of depressive symptoms were associated with female gender, lower education, family dysfunction, poor doctor–patient communication, and TB-related stigma. This study shows that the prevalence of depressive symptoms among internal migrants with TB is high in China. Targeting interventions and treatment of depressive symptoms among internal migrants with TB are needed.